CHARACTERISTICS OF PATIENTS WITH B-CELL NON-HODGKIN LYMPHOMA AND HEPATITIS B VIRUS INFECTION AT THE HEMATOLOGY AND BLOOD TRANSFUSION CENTER, BACH MAI HOSPITAL - Nguyen Thi Hang; Hoang Thi Hong; Nguyen Tuan Tung (Tạp chí Y học Quân sự, 2026)
Objectives: To describe the clinical and laboratory characteristics of B-cell non-Hodgkin lymphoma patients with hepatitis B virus infection at the Hematology and Blood Transfusion Center, Bach Mai Hospital. Subjects and methods: A descriptive study was conducted on 32 B-cell non-Hodgkin lymphoma patients with hepatitis B virus infection, treated at the Hematology and Blood Transfusion Center, Bach Mai Hospital, from January 2022 to January 2025. Results: The average age of patients was 58.5 years, with a male/female ratio of ≈ 1.3/1. The most common clinical manifestations were lymphadenopathy (84.4%) and B symptoms (46.9%). The rate of bone marrow infiltration was 34.4%, and extranodal involvement was 59.4%. Laboratory characteristics: the rate of patients with positive HBsAg was 78.1%; HBsAg negative, anti-HBc total and anti-HBs positive was 21.9%. 20% of HBsAg positive patients had high HBV DNA levels (> 2,000 IU/ml). The rates of elevated liver enzymes and LDH were 21.9% and 56.2%, respectively. The rates of anemia, leukopenia, and thrombocytopenia were 53.1%, 9.4%, and 21.9%, respectively. The predominant histopathological subtype was diffuse large B-cell lymphoma, accounting for 68.7% of cases, stage IV disease was also observed in 68.7% of patients. Conclusions: Further research is warranted to better characterize the clinical and laboratory features of patients with B-cell non-Hodgkin lymphoma and hepatitis B virus infection, thereby providing evidence to guide the development of appropriate therapeutic strategies.